THE INFLUENCE OF INTERNAL CONTROL ON THE PERFORMANCE OF THE FACTORY EMPLOYEE IN PT SINKONA INDONESIA LESTARI (PT SIL) (Study at the Factory) - Aldi Sabira; Icih Icih; Asep Kurniawan (STIESA Press, 2019)
This study aims to determine and examine the influence of Environmental Control, Risk Assessment, Control Activities, Information & Communication and Monitoring of Employee Performance. Data collection techniques are questionnaires, interviews, observation,documentation. The data used are primary data. The population in this study is PT SIL employees in the production and sample in this study as many as 100 respondents. Hypothesis testing uses multiple regression analysis The results of this study indicate: (1) the control environment does not affect employee performance; (2) risk assessment does not affect employee performance; (3) control activities have a positive effect on employee performance; (4) information & communication does not affect employee performance; (5) monitoring does not affect employee performance.